The power of paradox : impossible conversations - Locker, Markus (Value Inquiry Book Series, 2019)
This book argues that all truths systems include paradoxes. Paradoxes, such as found in the sciences, philosophy and religion offer themselves as mutually shared partners in a dialogue of arguably incommensurable truths on the basis of their underlying truth. Paradoxes leap beyond the epistemic border of individual truth claims. A dialogue of truths, grounded in paradox, reaches before, and at the same time past singular truths. A paradox-based dialogue of truths elevates the communication of disciplines, such as the sciences and religion, to a meta-discourse level from which differences are not perceived as obstacles for dialogue but as complementary aspects of a deeper and fuller truth in which all truths are grounded.